The University Experiences of Students with Learning Disabilities. Issue 2 (17th May 2016) - McGregor, Karla K.; Langenfeld, Natalie; Van Horne, Sam; Oleson, Jacob; Anson, Matthew; Jacobson, Wayne
Abstract : To explore the university experiences of students with learning disabilities (LD), 63, 802 responses to the 2014 Student Experience in the Research University Survey were analyzed. Compared to other students, those with self‐reported LD (5.96 percent) had difficulty with assignments and had more obstacles caused by nonacademic responsibilities and imposed by their skill levels. Students with self‐reported LD sensed more bias toward people with disabilities on campus, and they were less satisfied with their overall experience. Interactions between disability status and age suggested even more challenges for older students who self‐reported LD. Approximately one‐third of students who self‐reported LD received accommodations. The rate of accommodations was higher among individuals who were wealthy, who lived alone, and who were out‐of‐state students. Compared to students who self‐reported LD but reported no accommodations, those with accommodations had more contact with faculty and less difficulty with assignments.